'Not as single spies': a review of European Social Anthropology 2020. (4th December 2021) - Martin, Dominic
Abstract : This review article surveys all of the articles published in the major Anglophone European social anthropology journals in 2020. Taking a perspective from Joel Robbins' theorising of 'the anthropology of the good' as a critique of the primacy of 'dark anthropology', it highlights the rich range of ethnography and analysis recently produced. Focusing on the continuing interest in ontology, environment, relations and the problems inherent in anthropological comparison, the review article identifies how – during the crisis of the COVID‐19 pandemic – the discipline has continued to respond with vigour and resilience. An ongoing resurgence of the anthropology of religion is noted, as is the emergence of powerful emic exploration of such global phenomena as care, debt and corporate capitalism. The review article concludes with a reflection on the ideological and epistemological challenges social anthropology continues to face, both in the academy and more widely. 'Pas comme des espions célibataires': une revue de l'anthropologie sociale européenne 2020: Cet article passe en revue tous les articles publiés dans les principales revues européennes anglophones d'anthropologie sociale en 2020. S'inspirant de la théorie de Joel Robbins sur 'l'anthropologie du bien' comme critique de la primauté de 'l'anthropologie sombre', il met en évidence la richesse des ethnographies et des analyses produites récemment. En se concentrant sur l'intérêt continu pour l'ontologie, l'environnement, les relations et les problèmes inhérents à la comparaison anthropologique, l'article identifie comment – pendant la crise de la pandémie COVID 19 – la discipline a continué à répondre avec vigueur et résilience. On note une résurgence continue de l'anthropologie de la religion, ainsi que l'émergence d'une exploration émique puissante de phénomènes mondiaux tels que les soins, la dette et le capitalisme d'entreprise. L'article de synthèse se termine par une réflexion sur les défis idéologiques et épistémologiques auxquels l'anthropologie sociale continue d'être confrontée, tant au sein du milieu universitaire que dans un cadre plus large.